Bodyguard most wanted - Garbera, Katherine (Garbera, Katherine. Price security., 2023)
"When Nicholas DeVere's bodyguard is murdered, Luna Urban takes on the task of protecting the tabloid-famous billionaire. Her task is complicated by the fact that, having already survived countless attempts on his life, Nick feels invulnerable. And, after one electric kiss, the attraction between them becomes a dangerous distraction. Will his recklessness be his undoing--or will her feelings leave her fatally compromised?" --